Fluid management in chronic kidney disease: what is too much, what is the distribution, and how to manage fluid overload in patients with chronic kidney disease?. Issue 6 (November 2020) - de Ruiter, Anna; Bello, Aminu; Braam, Branko
Abstract : Purpose of review: Assessment of fluid status to reach normovolemia in patients with chronic kidney disease (CKD) continues to be a tough task. Besides clinical observation, technological methods have been introduced, yet, the best approach is still uncertain. The present review looks at fluid overload in CKD from three perspectives: the critical fluid threshold leading to adverse cardiovascular outcomes, fluid distribution and its clinical correlates, and direct effect of fluid overload on vascular function related to disturbance of the sodium–skin axis and endothelial glycocalyx dysfunction. Recent findings: To determine fluid status, both the absolute and relative fluid overload is used as parameter in clinical practice. In addition, the definition of fluid overload is ambivalent and its relation to symptom burden has not been studied well. Studies on the impact of distribution of fluid are scarce and the limited evidence suggests differences based on the cause of CKD. So far, no standardized technologies are available to adequately determine fluid distribution. After discovering the 'third compartment' of total body sodium in skin and muscle tissue and its potential direct effect on vascular function, other biomarkers such as VEGF-C are promising. Summary: We propose a multimodal clinical approach for volume management in CKD. Because there are currently no studies are available demonstrating that correction of fluid overload in CKD will lead to better outcome, these are strongly needed.